Analyses corrosion prediction software for CO2 corrosion of carbon steel using statistical formulas - Asmara, Y. P.; Sutjipto, A. G. E.; Siregar, J. P.; Kurniawan, Tedi; Jamiluddin, Jaafar (International Journal of Mechanical Engineering and Robotics Research, 2019)
The statistical formulas are capable tools to find a regression of corrosion rate effectively among combining factors. One type of statistical model which is response surface methodology (RSM) has shown a proven method in minimizing number of running. Through this technique, this research study predicting corrosion rate of carbon steel as effects of pH, CO 2 pressure and temperature. It can be used to run 3 dependent factors, 3 level experiment with only 16 number of running. The result reveals that NORSOK corrosion prediction software with second order model regression has 98 % of coefficient determination. Model prediction of Cassandra has 99.3% of coefficient determination. Second order model also has been verified with experimental data which shows a good correlation